Using Intervention Mapping for Program Design and Production of iCHAMPSS: An Online Decision Support System to Increase Adoption, Implementation, and Maintenance of Evidence-Based Sexual Health Programs - Peskin, Melissa F.; Hernandez, Belinda F.; Gabay, Efrat K.; Cuccaro, Paula; Li, Dennis H.; Ratliff, Eric; Reed-Hirsch, Kelly; Rivera, Yanneth; Johnson-Baker, Kimberly; Emery, Susan Tortolero; Shegog, Ross (Frontiers in Public Health, 2017)
In Texas and across the United States, unintended pregnancy, HIV, and sexually transmitted infections (STIs) among adolescents remain serious public health issues. Sexual risk-taking behaviors, including early sexual initiation, contribute to these public health problems. Over 35 sexual health evidence-based programs (EBPs) have been shown to reduce sexual risk behaviors and/or prevent teen pregnancies or STIs. Becauses more than half of these EBPs are designed for schools, they could reach and impact a considerable number of adolescents if implemented in these settings. Most schools across the U.S. and in Texas, however, do not implement these programs. U.S. school districts face many barriers to the successful dissemination (i.e., adoption, implementation, and maintenance) of sexual health EBPs, including lack of knowledge about EBPs and where to find them, perceived lack of support from school administrators and parents, lack of guidance regarding the adoption process, competing priorities, and lack of specialized training on sexual health. Therefore, this paper describes how we used Intervention Mapping (Steps 3 and 4, in particular), a systematic design framework that uses theory, empirical evidence, and input from the community, to develop iCHAMPSS (CHoosing And Maintaining Effective Programs for Sex Education in Schools), an online decision support system to help school districts adopt, implement, and maintain sexual health EBPs. Guided by this systematic intervention design approach, iCHAMPSS has the potential to increase dissemination of sexual health EBPs in school settings.